2018
DOI: 10.1016/j.astropartphys.2018.04.005
|View full text |Cite|
|
Sign up to set email alerts
|

Direct measurement of neutrons induced in lead by cosmic muons at a shallow underground site

Abstract: Neutron production in lead by cosmic muons has been studied with a Gadolinium doped liquid scintillator detector. The detector was installed next to the Muon-Induced Neutron Indirect Detection EXperiment (MINIDEX), permanently located in the Tübingen shallow underground laboratory where the mean muon energy is approximately 7 GeV. The MINIDEX plastic scintillators were used to tag muons; the neutrons were detected through neutron capture and neutron-induced nuclear recoil signals in the liquid scintillator det… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
(34 reference statements)
1
9
0
Order By: Relevance
“…The neutron yield predicted by GEANT4 for muon induced interactions in a low-A target, as organic liquid scintillator, was found to agree with the experimental results from KamLAND within 10% [22]. As for neutron production in high-A materials, the recent work of [23,24] reports that GEANT4 under-estimates it by a factor of 3-4 in Pb for cosmic muons at shallow depth ( E µ =7 GeV). However, [21] shows that GEANT4 slightly over-estimates the neutron production in Pb in a deep underground laboratory ( E µ = 260 GeV) by 25% and that the choice of the physics list has a < 5% impact.…”
Section: Monte Carlo Implementationsupporting
confidence: 56%
“…The neutron yield predicted by GEANT4 for muon induced interactions in a low-A target, as organic liquid scintillator, was found to agree with the experimental results from KamLAND within 10% [22]. As for neutron production in high-A materials, the recent work of [23,24] reports that GEANT4 under-estimates it by a factor of 3-4 in Pb for cosmic muons at shallow depth ( E µ =7 GeV). However, [21] shows that GEANT4 slightly over-estimates the neutron production in Pb in a deep underground laboratory ( E µ = 260 GeV) by 25% and that the choice of the physics list has a < 5% impact.…”
Section: Monte Carlo Implementationsupporting
confidence: 56%
“…When considering the matching between simulation and underground neutron flux data, it is important to note that it was recently reported that GEANT4 simulations underpredicted the flux of (μ, n) neutrons [28] in a laboratory with just 13 m.w.e. rock overburden.…”
Section: B Comparison Of Data and Simulationmentioning
confidence: 99%
“…Other work, for example, concentrates on thermal neutrons [22,23], shows only one [24] to three energy bins [25] or a limited energy range [26], or does not present a deconvoluted neutron energy spectrum [27]. It was reported that the flux of muon-induced neutrons seems to be underpredicted by GEANT4 Monte Carlo simulations with the standard physics list [28], whereas FLUKA simulations seemed to fare better [29].…”
Section: Introductionmentioning
confidence: 99%
“…The muon data developed here will be used in forthcoming work [32] addressing the recent debate on muoninduced neutrons underground [33]. In addition, it will be instrumental for designing an active veto for underground nuclear astrophysics experiments planned in Felsenkeller tunnels VIII and IX [25].…”
Section: Introductionmentioning
confidence: 99%